Implementasi Model Inquiry Training Berbasis Learning Cycle 5E dalam Meningkatan Keterampilan Berpikir Kritis pada Konsep Pencemaran Air - Andelina Devi; Yuni Arfiani; Mobinta Kusuma (JPMP, 2020)
This study aims to determine the effectiveness of the 5E-based inquiry training model (engagement, exploration, explanation, elaboration and evaluation) in improving students' critical thinking skills on the concept of water pollution. The population of this study were students of class VII of one of the state junior high schools in Bumijawa for the 2019/2020 school year. The sample selection was carried out by using purposive sampling technique. The research design was a pretest-posttest with data collection methods using a multiple choice test. Analysis of critical thinking skills by calculating the difference between the pretest and posttest using the N-gain test. The results of the N-Gain analysis obtained that the experimental class was 0.42 with moderate criteria and the control class was 0.26 with low criteria, it was concluded that the 5E-based inquiry training model was effective in improving critical thinking skills seen from the percentage of students who achieved KKM by 78%.